Português (Colloquium Agrariae. ISSN: 1809-8215, 2019)
The use of saline water in the production of greenery is one of the challenges for producers, since the salt stress causes decrease in production and crop yield. The aim, with this work, is to evaluate the growing culture of Arugula in different substrates and levels of saline water. The experiment was conducted in a greenhouse of the Agricultural Sciences Center of the Federal University of Alagoas, located in the municipality of Rio Largo, AL.The delineation was entirely randomised in factorial arrangement 3 x 5. The treatments consisted of three substrates (SUB1 = soil; SUB2 = sand + worm humus + soil; Sub3 = filter cake + sand + soil) and five levels of saline water (0.5; 1.5; 2.5; 3.5 and 4.5 dS m-1) with four repetitions. Were evaluated the following rate of growth: plant Height, number of leaves, leaf area and dry mass of shoots and fresh pasta from the shoot, to 40 days after transplanting. The growth rates of the variety of Arugula APRECIATTA were reduced with the increase of the electrical conductivity of the water. However, the substrates with higher organic matter content decreased the harmful effects of salinity, being a viable alternative for the cultivation of this vegetable under saline conditions.